Cultivating Pawongan Values in an Eighth-Grade English Textbook English for Nusantara: A Strategy to Strengthen Character Education - Luh Rista Hardiantini; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti; I Gusti Ngurah Agung Wijaya Mahardika; Ni Nyoman Artini (Universitas Pendidikan Ganesha, 2025)
Moral degradation influences the unstable relationship between humans. Maintaining a harmonious relationship among fellow humans is essential to avoid more serious problems. Therefore, the study aims to explore and present the Pawongan values in the eighth-grade junior high school textbook entitled English for Nusantara to recognize how the textbook involves character education development. The subject of the study was the content provided in the textbook, which means it is a content analysis research. The study utilised qualitative research procedures proposed by Miles, Huberman, and Saldana (2014). Data collection and analysis are conducted repeatedly and simultaneously through data collection, condensation, display, and conclusion drawing and verification. It was discovered that the Pawongan value is present in the home, school, and society. Pawongan values across those contexts internalize positive character development for students to be more respectful, sympathetic, empathetic, tolerant, solid, and equal. Therefore, the study shows that the concept of Pawongan in Tri Hita Karana contributes to character development through a local wisdom approach.